2014
DOI: 10.1007/s00436-014-4061-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and micro-habitats utilized by lizards determine the composition of their endoparasites in the semiarid Caatinga of Northeast Brazil

Abstract: Trophic networks can have architectonic configurations influenced by historical and ecological factors. The objective of this study was to analyze the architecture of networks between lizards, their endoparasites, diet, and micro-habitat, aiming to understand which factors exert an influence on the composition of the species of parasites. All networks showed a compartmentalized pattern. There was a positive relation between diet and the diversity of endoparasites. Our analyses also demonstrated that phylogeny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 42 publications
5
70
0
5
Order By: Relevance
“…Although it had been originally described as a parasite of A. ameiva, we recorded both P. pollicaris and H. brasilianus as new hosts for this species. Other records of hosts for P. lutzi were also reported in the literature Ávila et al 2010Brito et al 2014b): Ameivula abaetensis (Dias, Rocha & Vrcibradic, 2002) Barbour, 1909, L. ornatus Koslowsky, 1898, L. quilmes Etheridge, 1993, Tropidurus guarani, T. semitaeniatus, T. hispidus, T. itambere Rodrigues, 1987, T. torquatus (Wied, 1820), H. agrius, L. klugei, G. geckoides, Micrablepharus maximiliani (Reinhardt & Lütken, 1862 and Salvator merianae (Duméril & Bibron, 1839) [= Tupinambis merianae]. Given that P. lutzi has a heteroxenic life cycle, its intermediate host is probably a food item that is consumed by all sampled lizards in our study area.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Although it had been originally described as a parasite of A. ameiva, we recorded both P. pollicaris and H. brasilianus as new hosts for this species. Other records of hosts for P. lutzi were also reported in the literature Ávila et al 2010Brito et al 2014b): Ameivula abaetensis (Dias, Rocha & Vrcibradic, 2002) Barbour, 1909, L. ornatus Koslowsky, 1898, L. quilmes Etheridge, 1993, Tropidurus guarani, T. semitaeniatus, T. hispidus, T. itambere Rodrigues, 1987, T. torquatus (Wied, 1820), H. agrius, L. klugei, G. geckoides, Micrablepharus maximiliani (Reinhardt & Lütken, 1862 and Salvator merianae (Duméril & Bibron, 1839) [= Tupinambis merianae]. Given that P. lutzi has a heteroxenic life cycle, its intermediate host is probably a food item that is consumed by all sampled lizards in our study area.…”
Section: Discussionmentioning
confidence: 55%
“…Currently, there are 23 genera of helminths recognized as parasites of the lizard families Phyllodactylidae and Gekkonidae (Anjos et al 2005;Ávila & Silva 2010;Ávila et al 2010;Brito et al 2014a;Sousa et al 2014;Cazorla & Morales Moreno 2015;Bezerra et al 2016; this study); for the Caatinga biome, about 10 species of helminths have already been reported with a prevalence above 50% (Anjos et al 2005;Avila et al 2012;Brito et al 2014b;Sousa et al 2014; this study), and there were four helminth species with prevalences below 60% for deserts and coastal areas in Peru (Goldberg & Bursey 2010); two species had prevalences of 33.3% in the Brazilian Amazon forest (Ávila & Silva 2013); two species had prevalences up to 22.8% in the Atlantic Forest (Ávila et al 2010;Almeida-Gomes et al 2012); and three helminth species had prevalences below 15% for the tropical thorny mountain areas of Venezuela (Cazorla & Morales Moreno 2015). Notwithstanding that some genera and species of helminths were previously reported for different biomes as parasites of geckos, as S. oxkutzcabiensis and all species of the genera Oochoristica and Parapharyngodon, almost all prevalences registered for them were below that obtained for the Caatinga biome [e.g., Oochoristica sp.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Salvator merianae has been well reported as a host for the nematodes of the family Physalopteridae in Brazil, as follow: P. bainae (Pereira et al, 2014); P. lutzi (Brito et al, 2014b); P. retusa , and P. tupinambae (Pereira et al, 2012). In addition, P. lutzi also infects the stomach of the following lizards: Ameiva ameiva (Linnaeus, 1758) (Ribas et al, 1998); C. abaetensis Dias, Rocha andVrcibradic, 2002 (Dias et al, 2005); (Ribas et al, 1995); Enyalius bilineatus Duméril and Bibron, 1837 (Vrcibradic et al, 2007); Eurolophosaurus nanuzae (Rodrigues, 1981) (Fontes et al, 2003); Tropidurus itambere (Rodrigues, 1987) (Van Sluys et al, 1994; T. torquatus (Wied-Neuwied, 1820) (Vrcibradic et al, 2000); T. oreadicus Rodrigues, 1987Rodrigues, (Ávila et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…in areas of the Caatinga, in the Brazilian semiarid (Brito et al, 2014a); Cruzia travassosi Khalil and Vogelsang, 1932 in areas of the Amazon Forest, Cerrado and Pantanal ; Diaphanocephalus galeatus (Rudolphi, 1819) in areas of coastal biomes in the Archipelago of Fernando de Noronha and the Amazon Forest, Cerrado and Pantanal (Ramalho et al, 2009;; Physaloptera tupinambae Pereira, Alves, Rocha, Souza Lima and Luque, 2012 and P. bainae Pereira, Alves, Rocha, Souza Lima and Luque, 2014 in the municipality of Juiz de Fora -MG in areas of the Atlantic Forest (Pereira et al, 2012(Pereira et al, , 2014; P. lutzi Cristofaro, Guimarães and Rodrigues, 1976 in areas of the Caatinga, in the Brazilian semiarid (Brito et al, 2014b); P. retusa Rudolphi, 1819 in the Amazon Forest, Cerrado and Pantanal ; Spinicauda spinicauda (Olfers, 1819) in coastal biomes, and the Amazon Forest, Cerrado and Pantanal (Ramalho et al, 2009;; and a species of Cestoda not identified, Oochoristica sp. in coastal biomes in the Archipelago of Fernando de Noronha (Ramalho et al, 2009).…”
Section: Introductionmentioning
confidence: 99%